Drug-induced inhibition of phosphorylation of STAT5 overrides drug resistance in neoplastic mast cells - Peter, Barbara; Schwaab, Juliana; Jawhar, Mohamad; Reiter, Andreas (Leukemia, 2018)
Systemic mastocytosis (SM) is a mast cell (MC) neoplasm with complex pathology and a variable clinical course. In aggressive SM (ASM) and MC leukemia (MCL), responses to conventional drugs are poor and the prognosis is dismal. R763 is a multi-kinase inhibitor that blocks the activity of Aurora-kinase-A/B, ABL1, AKT and FLT3. We examined the effects of R763 on proliferation and survival of neoplastic MC. R763 produced dose-dependent inhibition of proliferation in the human MC lines HMC-1.1 (IC50 5-50 nM), HMC-1.2 (IC50 1-10 nM), ROSAKIT WT (IC50 1-10 nM), ROSAKIT D816V (IC50 50-500 nM) and MCPV-1.1 (IC50 100-1000 nM). Moreover, R763 induced growth inhibition in primary neoplastic MC in patients with ASM and MCL. Growth-inhibitory effects of R763 were accompanied by signs of apoptosis and a G2/M cell cycle arrest. R763 also inhibited phosphorylation of KIT, BTK, AKT and STAT5 in neoplastic MC. The most sensitive target appeared to be STAT5. In fact, tyrosine phosphorylation of STAT5 was inhibited by R763 at 10 nM. At this low concentration, R763 produced synergistic growth-inhibitory effects on neoplastic MC when combined with midostaurin or dasatinib. Together, R763 is a novel promising multi-kinase inhibitor that blocks STAT5 activation and thereby overrides drug-resistance in neoplastic MC.
Publishek 29 November 2017
Gesehen am 25.07.2018